Improving Methodological Approaches to Assessing the Effectiveness of using Fixed Capital in Railway Transport - Abdulaziz Gulamov; Odil Abdurakhmanov; Said Shjaumarov (International Journal on Orange Technologies, 2021)
The article discusses the problems of economic valuation of fixed capital, in particular, considers the most important tasks of the renovation process, the problems of creating and putting into operation more advanced models of tools for ensuring stable safety of train traffic, analyzed the qualitative and quantitative indicators of the use of fixed capital, made a conclusion about estimates of fixed assets in railway transport.